2004
DOI: 10.1093/bja/aeh083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perioperative α 1 block on haemodynamic control during laparoscopic surgery for phaeochromocytoma

Abstract: Perioperative alpha(1) block using i.v. urapidil is a safe and efficient alternative during surgical management of phaeochromocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 27 publications
4
73
1
6
Order By: Relevance
“…In our earlier study with low doses of urapidil, the incidence of hypertensive episodes during tumour resection was 66%. 7 Assuming that it would decrease to 56% with high doses, 18 patients in each group were required for the paired t-test with a ¼ 0.05, b ¼ 0.1 (power: 90%) and standard deviation ¼ 12%. Categorical data were compared using w 2 and Fisher's exact tests where appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier study with low doses of urapidil, the incidence of hypertensive episodes during tumour resection was 66%. 7 Assuming that it would decrease to 56% with high doses, 18 patients in each group were required for the paired t-test with a ¼ 0.05, b ¼ 0.1 (power: 90%) and standard deviation ¼ 12%. Categorical data were compared using w 2 and Fisher's exact tests where appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…7 Briefly, after radial artery cannulation, general anaesthesia was induced using i.v. propofol 2 mg kg Àl and sufentanil 0.8 mg kg…”
Section: Anaesthesia and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to calcium channel blockers could be the use of alpha-1 blockers, particularly the short acting agent urapidil, which is characterised by antiserotoninergic properties that block reflex tachycardia in response to a decrease in arterial pressure. Its peri-operative haemodynamic control has been evaluated in 18 patients undergoing laparoscopic phaeochromocytoma resection [10]. In that study, a continuous i.v.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Parnaby et al showed that laparoscopic adrenalectomy for pheochromocytoma was indeed associated with increased episodes of severe intraoperative hypertension (SBP >200-220 mmHg) when compared to the laparoscopic resection of other adrenal tumors (47). Interestingly, a creation of peritoneum has been shown to increase catecholamines release which may result in hemodynamic instability (35,48,49). Moreover, case control studies confirmed that in terms of hemodynamic instability laparoscopic approach is equal to open procedure (50,51).…”
Section: Intraoperative Considerationsmentioning
confidence: 99%